Alteration of Cholesterol Sulfate/Seminolipid Ratio in Semen Lipid Profile of Men With Oligoasthenozoospermia - Lopalco, Patrizia; Vitale, Rita; Cho, Yoon Sung; Totaro, Pasquale; Corcelli, Angela; Lobasso, Simona (Frontiers in Physiology, 2019)
The reduction of sperm motility and count, or oligoasthenozoospermia, is one of the major causes of reduced fertility or infertility in men. Lipid composition of spermatozoa is important in determining their functional characteristics, in particular on motility, acrosomal exocytosis or fusogenic properties of the sperm. Here we investigated the levels of semen lipids in 11 infertile patients with severe oligoasthenozoospermia and 9 normozoospermic subjects with normal motility values. Sperm polar and neutral lipids were analysed by thin-layer chromatography (TLC) and matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-TOF/MS). Semen of patients with oligoasthenozoospermia showed a reduction of the degree of fatty acids unsaturation in the phospholipids chains that might affect the membrane fluidity. Furthermore, a significant higher cholesterol sulfate/seminolipid ratio was found in semen of oligoasthenozoospermic patients than in subjects with normal motility values, suggesting a critical role of sulfolipids in semen quality. The results may facilitate the understanding of the role of lipids on male fertility and offer interesting perspectives to find innovative treatment for oligoasthenozoospermia.